First satellite able to re-enter the atmosphere in a controlled way. (Research'eu results magazine)
D-Sat is the first satellite in history that will ends its mission by re-entering Earth's atmosphere in a safe and controlled way, burning up instead of becoming new debris. The satellite, which was launched on Friday, 23 June 2017, used a decommissioning and re-entry device created by the EU-funded D3 project.